The Effects of Foreign Direct Investments on Industrialization: A Comparative Approach between the Franc and the Non-Franc Zone - Ngouhouo, Ibrahim; Ewane, Etah Ivo (Asian Journal of Economic Modelling, 2020)
The aim of this paper is to contribute to literature by showing explicitly the direct and the indirect effect of foreign direct investment on industrialization by comparing the franc and the non-franc zone countries in Africa. Our empirical evidence has made use of data from 12 countries of the franc zone and 11 countries of the non CFA zone making a total of 23 African countries spanning from 1990-2017. After carrying out preliminary test to permit us choose the appropriate method, we employed the Pooled Mean Group estimation technique for both groups of countries, which is appropriate for drawing conclusions from dynamic heterogeneous panels by considering long-run equilibrium relation. The results show that FDI has a significant positive effect on industrialization within the franc zone countries mean while it has a negative but significant effect on industrialization within the non-zone franc countries. In other words, the results reveal that within the franc zone, industrialization is more favored when compared to the non-franc zone countries. Practical and theoretical implications are discussed.